Generating Cost Efficiency Charts - Harasani, Wail I. (International Journal of Advanced Research in Engineering; Vol 1 No 3 (2015): International Journal of Advanced Research in Engineering, 2015)
The aim of this paper is to construct with a help of a local airline a cost efficiency charts, for three given aircraft to operate in three independent sectors. These chart are generated by an Excel code, the efficiency charts would be useful for airlines and fleet planners in their decision making process.